2004
DOI: 10.1002/pssc.200304385
|View full text |Cite
|
Sign up to set email alerts
|

High field induced spin reorientations in Ho 0.24 Y 2.76 Fe 5 O 12

Abstract: Some precise magnetization measurements have been performed on Ho 0.24 Y 2.76 Fe 5 O 12 single crystals under static magnetic fields up to 16 Tesla and in the temperature range (2-30 K). As previously observed in pulsed magnetic fields, the change from the spontaneous ferrimagnetic structure in zero magnetic field to the fully ferromagnetic one in high field, takes place through several intermediate phases separated by step-like magnetization jumps. Whole H-T phase diagrams have been determined for the three m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 5 publications
(4 reference statements)
0
7
0
Order By: Relevance
“…The chemical composition was checked using a scanning microscope (JSM-840A), electronic microprobe and chemical analysis and also by checking carefully the specific magnetization of each sample in the low field range. The results of these different methods show a greater dispersion than for the previously studied compound (x = 0.24 ± 0.01) [8] and the composition was found to vary from x = 0.41 to 0.45. So we take x = 0.43 ± 0.02, and all the magnetization results are reported in Bohr magnetons per Ho 0.43 Y 2.57 Fe 5 O 12 formula unit.…”
Section: Experimental Details and Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…The chemical composition was checked using a scanning microscope (JSM-840A), electronic microprobe and chemical analysis and also by checking carefully the specific magnetization of each sample in the low field range. The results of these different methods show a greater dispersion than for the previously studied compound (x = 0.24 ± 0.01) [8] and the composition was found to vary from x = 0.41 to 0.45. So we take x = 0.43 ± 0.02, and all the magnetization results are reported in Bohr magnetons per Ho 0.43 Y 2.57 Fe 5 O 12 formula unit.…”
Section: Experimental Details and Resultsmentioning
confidence: 65%
“…Previous experiments on related compounds in pulsed fields [4][5][6][7] or in static fields [8] have shown that, at sufficiently low temperature, the increase of the applied field H gives rise to 'orientational' phase transitions with step-like magnetization curves, corresponding to the passage from the initial ferrimagnetic state to the ferromagnetic saturated state through several canted phases. The number of these transitions depends on the orientation of the external field with respect to the crystallographic axes.…”
Section: Introductionmentioning
confidence: 99%
“…At T = 0 K, the three Ho moments are equal, implying that during these discontinuous transitions M Ho jumps from one type of 111 direction to another, with simultaneous and appropriate change in M Fe orientation. This model has been useful for a qualitative description of the different orientational phases and the transitions involved between them in such diluted rare-earth compounds, but it does not account quantitatively for all the observations [4,5,10,11]. In particular, when the temperature is raised the observed magnetic transitions become smoother and smoother and vanish all together more quickly at a critical temperature T * (=18.9 K, present work).…”
Section: Introductionmentioning
confidence: 80%
“…Here n is the isotropic molecular-field coefficient. We deduced earlier [10] that its value can be taken equal to 2.2 T mol/μ B (i.e. H mol = 11 T).…”
Section: Phase Diagrams and Discussionmentioning
confidence: 97%
See 1 more Smart Citation